2011
DOI: 10.1007/s10067-011-1757-7
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of low-level laser therapy with exercise on subacromial syndrome: a randomised, double-blind, controlled trial

Abstract: The subacromial syndrome is the most common source of shoulder pain. The mainstays of conservative treatment are non-steroidal anti-inflammatory drugs and exercise therapy. Recently, low-level laser therapy (LLLT) has been popularized in the treatment of various musculoskeletal disorders. The aim of this study is to evaluate the additive effects of LLLT with exercise in comparison with exercise therapy alone in treatment of the subacromial syndrome. We conducted a randomised clinical study of 80 patients who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 30 publications
3
70
0
Order By: Relevance
“…In all these studies conducted for SIS, LLLT was not superior to other interventions. In contrast to these studies, Abrisham et al (23) reported that LLLT combined with exercise was more effective than exercise therapy alone in pain relief and increased shoulder ROM. In a systematic review, Green et al (24) indicated that exercise therapy was effective in recovery from rotator cuff disease, but laser therapy was not effective for rotator cuff tendinitis.…”
Section: Dıscussıonmentioning
confidence: 93%
“…In all these studies conducted for SIS, LLLT was not superior to other interventions. In contrast to these studies, Abrisham et al (23) reported that LLLT combined with exercise was more effective than exercise therapy alone in pain relief and increased shoulder ROM. In a systematic review, Green et al (24) indicated that exercise therapy was effective in recovery from rotator cuff disease, but laser therapy was not effective for rotator cuff tendinitis.…”
Section: Dıscussıonmentioning
confidence: 93%
“…Both used LLLT combined with exercise. One used placebo laser with exercise as the comparison group, 51 and the other used ultrasound and hot packs with exercise. 69 One found significant improvement in pain (VAS) in the active LLLT group, but not in the placebo group.…”
Section: Kinesiotapingmentioning
confidence: 99%
“…69 One found significant improvement in pain (VAS) in the active LLLT group, but not in the placebo group. 51 The other trial found a within-group improvement in pain (VAS) and function (Shoulder Pain and Disability Index [SPADI]) for both LLLT plus exercise and ultrasound plus exercise, but no significant difference between groups. 69 …”
Section: Kinesiotapingmentioning
confidence: 99%
“…1 Shoulder pain can be caused by any number of underlying conditions including subacromial impingement syndrome, rotator-cuff tendinitis, and biceps tendinitis. 2,3 Regardless of the specific pathology, pain is generally the number 1 symptom associated with shoulder injuries and can severely affect daily activities 4 and quality of life 5,6 of patients with these conditions. Two of the primary goals in the treatment of these conditions is reducing pain and increasing shoulder range of motion (ROM).…”
mentioning
confidence: 99%
“…7,8 In addition, these exercise programs have been supplemented with other interventions including nonsteroidal anti-inflammatory drugs, corticosteroid injections, manual therapy, activity modification, and a wide array of therapeutic modalities (eg, cryotherapy, EMS, ultrasound). 2,3,7 Recently, low-level laser therapy (LLLT) has been used as an additional modality in the conservative management of patients with shoulder pain. 3,9,10 However, the true effectiveness of LLLT in decreasing pain and increasing function in patients with shoulder pain is unclear.…”
mentioning
confidence: 99%